Purposeful practice: Constraints and temperament impact on physical performance of collegiate Division II soccer athletes - Hinchman, T.; Taylor, C. D.; Lange, E. J.; Meachum, M. (The Sport Journal, 2023)
This quantitative quasi-experimental study examined differences in mean and median differences of millennial soccer athlete`s performance. Research indicates that millennials struggle with complex tasks due to their fear of failure. Individual productivity has been shown to be positively influenced by the use of designed constraints. The study employed the C-BMN framework and the GPAI to analyze data pertaining to constraint-type and its influence on the productivity of 18 soccer players. Individual components teamwork and trapping showed statistical significance during the intervention, while positioning, passing, and dribbling did not. The overall GPAI showed statistical significance between the control and both constraint types. A two-mixed ANOVA showed no statistically significant interaction between constraints and temperaments however only 72% of participants completed the temperament assessment.